Correlation between serum electrolyte levels and brain stem evoked response audiometry in chronic renal failure: a pilot study - Munjal, Manish; Singh, Karanpreet; Chopra, Parth; Munjal, Shubham; Chopra, Hemant; Mathur, Aditi; Grewal, Mehtab (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The effect of electrolyte imbalance on hearing thresholds and its objective manifestation, as delayed latencies or inter-peak intervals in evoked response audiometry is studied. Methods: The present prospective study was undertaken in a period of one and a half years, to analyze the audiological profile in patients of chronic renal failure and renal allograft recipients. 60 patients were randomly selected from the out- patient and indoor services of nephrology, urology and oto-rhino-laryngology, Dayanand Medical College and Hospital, Ludhiana. Brain stem evoked response audiometry was performed and the latencies were tabulated. Results: A significant delay in the absolute latency of wave V was noted in hyponatremic patients of CRF on comparison with patients of CRF having a normal serum Na+ levels. The I-V interpeak interval was also seen to be significantly delayed on comparison. A statistically significant delayed I-III inter-peak latency was also observed in hypernatremic patients in comparison to patients having a serum Na+ level in the normal range. No significance of serum creatinine levels and wave latencies was noted on comparison between the three categories of patients of CRF as categorized by their serum creatinine levels. Conclusions: There is a definite deterioration of the audiological function in patients of chronic kidney disease, and some reversal of these abnormalities following a successful renal transplantation; indirectly pointing towards uremic milieu being the culprit.